(untitled) (Global Scientific Review, 2022)
Free Learning program policy this made without reason. That said this program triggered too because see many complaints from parents to the ongoing education system During this. Freedom to learn is one effort for liberate method students and teachers in think and create. because it, we take idea design practice “Know Merdeka Curriculum Through Posters and Developing Creativity Student Through Activity Drawing and Pasting”. Tools and materials used ie paper cardboard, various picture about learn, double tip, and scissors. The reason we took design this for educate participant educate them knowing that learning no only in space class course, but can outside class for example like in the garden.